Assessing the genetic diversity of Ethiopian indigenous goat ecotypes at the hemoglobin locus and its associations with morphometric traits - Kebede Tilahun; Aberra Melesse; Simret Betsha (PLoS ONE, 2025)
Genetic variation is the baseline for viability, fitness, survivability, and improvement of livestock raised under diverse agroclimatic conditions. The study aimed to assess the genetic variation in the population of goats at the hemoglobin (Hb) locus and its association with morphometric traits. The blood samples were collected from 225 mature goats of both sexes. Morphometric traits, including body weight, chest girth, chest depth, body length, rump length, rump height, rump width, height at withers, fore canon circumference, and ear length, were measured to examine associations with the Hb genotype. The red blood cells were subjected to gel electrophoresis to determine hemoglobin variants. Hemoglobin polymorphisms were analyzed using the Pop gene (ver.32) and the associations with morphometric traits were analyzed using the statistical analysis system. Three Hb genotypes, HbAA, HbAB, and HbBB were detected with genotypic frequencies of 0.34, 0.47, and 0.19, respectively. HbAA was most frequent in highland goats (47%), while HbAB was the predominant genotype in lowland and midland populations. A significant deviation (p < 0.05) from the Hardy-Weinberg Equilibrium (HWE) was observed for the midland goats, while those in the lowland and highland were under HWE. The heterozygosity ranged from 0.36-0.61, indicating population variability and potential for genetic improvement. Hemoglobin showed significant (p < 0.05) influence on most of the morphometric traits in which goats with the homozygous HbBB genotype exhibited superior performance compared to other genotypes. In conclusion, hemoglobin polymorphism could be a viable option for assessing genetic diversity and may serve as a potential genetic marker to support selective breeding programs.